Allelopathic effect of Eucalyptus tereticornis clones on subabul (Leucaena leucocephala L.) - Tripathi, V.D.; Venkatesh, A.; Prasad, Rajendra; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
An investigation was conducted to explore the allelopathic effect of rhizosphere soil of Eucalyptus tereticornis on germination and seedlings growth of subabul (Leucaena leucocephala L.). The pot culture experiment consisted of rhizosphere soil from four clones of E. tereticornis (C3, C6, C7 and C10) collected at three distances viz., near base (O m), 1 m and 2 m from the tree base and control (devoid of E. tereticornis) at two depths viz.,0-15 and 15-30 cm. The rhizosphere soil toxicity was in the order of 0 m > 1 m> 2 m and the depths from tree-base. The inhibitory effect of soil depth in the orderof 15-30 cm > 0-15 cm. Among the clones, the maximum toxicity was exhibited by C7.